Peranan kepala sekolah dalam efektivitas pembelajaran daring dengan Google Sites di sekolah menengah atas - Triawan, Denny Wahyu (Sungging: Journal of Innovative, Cultural, Transdisciplinary Art and Kriya Discourse, 2023)
This study aims to analyze the role of the Principal in terms of policy, leadership and technology management in schools during the online learning process during the pandemic, and also to review the factors in the process. SMA Swadaya Bandung as the venue for this research during the 2020 academic year. The research uses a qualitative approach with the phenomenological method. Data collection techniques using questionnaires and interviews. The subjects used in this study were several teachers of SMA Swadaya Bandung. The results of this study indicate that the principal's leadership has an important role in influencing, mobilizing, developing and empowering all available resources by learning at SMA Swadaya Bandung using the whatsapp group application, google classroom, and google site. Offline learning is not implemented because it is still in a pandemic condition. The supporting factors for online learning at SMA Swadaya Bandung are gadgets, laptops, internet quotas, and TVRI broadcasts. While the inhibiting factors for online learning include the teacher not fully explaining the material and managing Google product facilities, the interests and motivation of students, and economic factors.